Climate anomalies and Price dynamics: Insights from Sub-Saharan African Currency Unions - (:unkn) unknown (My University, 2025)
This paper examines the dynamic impact of climate anomalies on consumer prices within two Sub-Saharan African (SSA) currency unions: the West African Monetary Union (WAMU) and the Central African Monetary Union (CAMU). Using a local projections method on a monthly panel dataset spanning 2002M1-2019M12, we find that temperature and precipitation anomalies lead to short-term increases in consumer prices of up to 1 percentage point and 0.1 percentage point, respectively, at the currency union level. Country-level estimations reveal significant heterogeneity, with some economies experiencing inflationary pressures lasting beyond two years. While countries' reliance on the agricultural sector appears to be the main transmission channel of these inflationary effects, interestingly, economic development, energy consumption, and political stability emerge as effective mitigating factors. Given the limited monetary policy autonomy of the two currency unions, targeted adaptation strategies-such as investments in climate-resilient agriculture and renewable energy-are essential to prevent these climate-related inflationary risks.
Keywords: African Research